Intravenous Augmentative Valproate Versus Delorazepam in Bipolar Patients With a Major Depressive Mixed Episode and Partial/Nonresponse to Oral Treatment: A Pilot Study. Issue 1 (January 2021) - Buoli, Massimiliano; Ceresa, Alessandro; Barkin, Jennifer L.; Weston, Carolina; Mucci, Francesco; Pozzoli, Sara; Esposito, Cecilia Maria
Abstract : Supplemental digital content is available in the text.